The Intention to Accept the Augmented Reality in Education: A Survey Study on Students’ Perspectives at the University of Mosul - Hamokhalil, Mohammed A. M. (PROSPECTIVE RESEARCHES, 2026)
The Augmented reality offers tremendous potential for developing the higher education sector, thus increasing its importance in education. It enables users to learn and train by creating interactive learning environments that allow students to learn, apply knowledge practically, and correct errors, thereby enhancing the quality of the educational process. This research aimed to investigate the factors influencing the behavioral intention of University of Mosul students towards accepting and adopting AR technologies in their studies. To achieve the study's objectives, an integrated research model was proposed, combining variables derived from the “Technology Acceptance Model (TAM)”, the “Unified Theory of Technology Acceptance and Use (UTAUT)”, and “Theory of Planned Behavior (TPB)”. The study focused on core dimensions, including (perceived ease of use, perceived usefulness, personal attitude, and social norms), in addition to psychological dimensions such as (immersion and perceived enjoyment). The study employed a descriptive analytical approach, using a validated questionnaire as the data collection tool. The sample consisted of 214 students from the University of Mosul's Colleges of Science and Engineering. To analyze the data and test the hypotheses, advanced statistical methods were used using (SPSS version 26) and structural equation modeling using (AMOS version 26). The research yielded several findings, most notably that the willingness to accept and adopt AR in education depends largely on the technical characteristics and practical value of AR technology, rather than on personal attitudes or social pressures. Based on these findings, the research recommends integrating realistic scenarios that simulate practical experiences or applied problems to enhance the engagement and realism of the learning process.